Systems of Commercial Turbofan Engines An Introduction to Systems Functions - Linke-Diesinger, Andreas (Springer Berlin Heidelberg : Imprint: Springer, 2008)
For the understanding of the operation of gas turbine engines used in aircraft, it is not enough to understand the basic operation of a gas turbine. It is also necessary to understand the operation and the design of its systems. This book provides an introduction to the systems of modern commercial turbofan engines. It is made for the reader who is familiar with the basics of aircraft gas turbine engine operation and is preparing him- or herself for the first engine type training. This book also offers a basic orientation through the numerous tubes, lines and system components installed on a complex turbofan engine. Within this book you will find information on the operation of engine systems, the functions of their components and the terminology used throughout the industry. The engine systems are explained using examples selected from today's engines. As a result, you will be made familiar with the current technology in this field. The examples include various engines from different manufacturers. Even if you have no engineering background, this book will provide you with comprehensible information and will help you to acquire a deeper knowledge of the operating principles at work in the systems of commercial turbofan engines. It is useful for the aircraft mechanic, the engineering student and for the student pilot.